Is Blood Flow Restriction During Warm-Up Able to Alter the Performance of Soccer Players? - Filho, Carlos Alberto Toledo Teixeira [UNESP]; de Oliveira, Enzo Vinícius Corrêa [UNESP]; Carneiro, Gislaine Rita [UNESP]; Vendrame, Julia Waszczuk [UNESP]; Pizzo, Eduardo [UNESP]; Da Silva, Gabriel Martins [UNESP]; da Silva, Gabriel Oliveira [UNESP]; da Silva Brandão, Guilherme Henrique [UNESP]; Vanderlei, Franciele Marques [UNESP] (Thieme, 2025)
We sought to evaluate the effects of a low-intensity warm-up with blood flow restriction (BFR) compared to low- and high-intensity warm-up on performance and perceptual responses. A randomized, controlled, crossover clinical trial was conducted with 33 soccer players, divided into three experimental conditions: warm-up at 30% of VO2 peak, warm-up at 80% of VO2 peak, and warm-up at 30% of VO2 peak combined with BFR at 80% of total occlusion pressure. Vertical jump and sprint tests, muscle pain, perception of effort, discomfort in relation to BFR, and myotonometry were measured before, immediately post, and 10 and 20 minutes post warm-up. No difference was observed between experimental conditions, and no interaction between conditions vs. moments for the performance. In the condition with BFR, there was a difference for the effort perceived and the perception of discomfort in relation to the BFR technique, indicating greater perception of effort and level of discomfort. For myotonometry, differences were found, indicating lower muscle elasticity in the condition with BFR. The low-intensity warm-up with BFR as well as the low- and high-intensity warm-up without BFR resulted in similar performances. Furthermore, although perception of discomfort was greater in the warm-up condition with BFR, it can be attenuated with different BFR protocols.